Temperature-mediated shifts in feeding behaviour and metabolism in an omnivorous rock pool prawn - Gustavo M. Martins; Christopher D. G. Harley; Ana Neto; Francisco Arenas (PLoS ONE, 2025)
Temperature is a key factor influencing metabolic processes and ecological interactions in ectothermic organisms, and can determine pathways of energy flow in food webs. In this study, we tested the hypothesis that omnivore diets shift away from carnivory and towards herbivory at warmer temperatures. Specifically, we investigated the effects of temperature on the feeding behaviour and metabolic activity of the omnivorous rock pool prawn Palaemon elegans Rathke, 1837, across three temperature regimes (15°C, 20°C, and 25°C) commonly encountered in intertidal rockpools of the Azores. Palaemon individuals were offered either algae ( Ulva muscoides ), amphipods ( Hyale perieri ), or a choice of both to assess feeding preferences. Our results demonstrate that temperature significantly influenced both the consumption of Ulva and Hyale , as well as prawn oxygen consumption. At lower temperatures (15°C), Palaemon consumed less Ulva when given a choice, while at higher temperatures (25°C), the consumption of Hyale decreased. Oxygen consumption increased significantly with temperature, indicating heightened metabolic activity in warmer conditions. These findings suggest that as temperatures rise, Palaemon may shift its feeding preferences towards herbivory, with potential implications for intertidal food webs in a warming climate. This study highlights the importance of temperature in shaping trophic interactions and food web structure, and underscores the need for further investigation into the long-term impacts of climate change on coastal ecosystems.